Penatalaksanaan Motor Relearning Programme (MRP) Pada Pasien Hemiparese Sinistra Post Stroke Non Haemoragik Stadium Recovery Di Rsal Ramelan Surabaya - Sari, Astuti Handoko; , Umi Budi Rahayu, S.Fis, M.Kes (2016)
Background: Non Haemoragik stroke is a stroke caused by blood circulation to the brain tissue that is stalled partly due to atherosclerosis (the accumulation of cholesterol in the walls of blood vessels) or blood-clot or emboli that has blocked a blood vessel to the brain. The treatment process or the perfect cure occurs in the recovery phase (recovery). In stroke patients, problematic recovery stages that arise among others are impairing balance, decreasing motor function side of the lesion, decreasing functional abilities and limitations of functional activity. One method of stroke rehabilitation is Motor Relearning Programme (MRP). MRP can improve learning and adaptation capacity of the brain so that the patient can learn normal motor function prior to the motion compensation, motion to prevent muscle imbalance and prevent useless to limb lesions Objective: To investigate the implementation of the method Motor Relearning Porgamme (MRP) in the case of non haemoragik stroke recovery stage can help improve balance, improve motor function side of the lesion and functional ability. Results: After treatment for 6 times the results an increase in the balance with the Berg Balance Scale T0: total value of 31, became T6: 41. Improving the ability of motor function with modifed Motor Assessment Scale T0: total value of 34, became T6: 38 and Improved ability of activity functional with Barthel index, T0: Total value of 95 into T6: 100. Conclusion: The method Motor Relearning Programme (MRP) can help improve balance, motor function side of lesion and functional ability.